Source apportionment of particulate matter 2.5 using positive matrix factorization (PMF) in the Philippine General Hospital - Enoveso, Rose Abigail D.
Source apportionment analysis was conducted on the data sets from a 2015 PM2.5 characterization study conducted by Lomboy et al. In the Philippine General Hospital (PGH). In the said study, daily PM2.5 samples were collected from October to December 2013 and from March to April 2014 at four sampling locations in the PGH. Sources of the PM2.5 were identified using the Positive Matrix Factorization (PMF), a receptor model. Over all, six types of sources were identified such as sodium and chlorine sources, sulfur sources, soil dust, biomass burning, and a mixed source. Four of these sources were obtained for the Pediatrics ward, and CENICU while five of these sources were identified for the Medicine ward and NICU. Using the type of ventilation as a stratification, five sources as well as their contributions to total PM Mass were identified for the naturally-ventilated wards namely sodium and chlorine sources (0.12ug/m3, 0.38%), sulfur sources (8.58 ug/m3, 28.74%), road dust (1.47 ug/m3, 4.92%), soil dust (0.71 ug/m3, 2.38%), and biomass burning (8.40 ug/m3, 28.13%) with an unaccounted mass of 10.58 ug/m3 or 35.45% of the total PM mass. On the other hand, four sources were identified for the mechanically-ventilated wards namely sodium and chlorine sources (0.35 ug/m3, 1.63%), sulfur sources (6.74 ug/m3, 31.7%), soil dust (1.07 ug/m3, 5.04%), and biomass burning (5.26 ugm3, 24.71%) with an unaccounted mass of 7.85 ug/m3 or 36.92% of the total PM mass. Only one of the six factors for all sites, sodium andchlorine sources, are contributed by indoor activities/contaminants, specifically by cleaning agents used in the hospital, while the rest are from outdoor air. Soil dust and sea salt were the only natural sources, leaving the others as anthropogenic. In this light, preventive and control measures may be formulated to minimize the contribution of anthropogenic source inside the hospital by improving the management of cleaning activities. For anthropogenic sources originating from outdoors, building insulation and ventilation systems may be reinforced. Seasonal variation was not established due to limited number of samples and sampling period, thus it is recommended to conduct another source apportionment study with more samples and sampling period of at least one year.